Unfractionated heparin selectively modulates the expression of CXCL8, CCL2 and CCL5 in endometrial carcinoma cells. - Marshall, Anne; Rom, Joachim; Schütz, Florian; Fluhr, Herbert (Anticancer research, 2016)
Abstract: BACKGROUND/AIM:This in vitro study analyzed the impact of heparins on expression of chemokines in human endometrial adenocarcinoma cell lines....